2D SEISMIC FORWARD MODELING OF SUBSURFACE WITH SHALLOW GAS CLOUD: A CASE STUDY FROM MALAY BASIN OFFSHORE - BIN RIZA FEISAL, SHEIKH MOHD. RAZI (Universiti Teknologi PETRONAS, 2014)
Poor quality of seismic data in the shallow gas cloud environment seems like a real challenge for seismic processing and imaging. Amplitude loss and sagging effect in the subsurface underneath the shallow gas cloud area are difficult to be handled during processing without understanding the factor that caused the real effect. Seismic forward modeling is capable to conduct a defined acquisition with different sourcereceiver geometry in a survey area using geophysical software instead of real acquisition with a fully crewed seismic vessel. The project will focus on the effect created by the shallow gas cloud in 2D seismic forward modeling based on real seismic and well log data taken from the study area in Malay Basin offshore. Synthetic seismic is generated by 2D acoustic modeling with the input of P-wave velocity, formation density and Q-value. The result of post-stack time migrated synthetic seismic is later on be compared with real seismic data at the similar study area in order to justify the anomalies present underneath shallow gas. It is justified the amplitude loss underneath the gas cloud area is influenced by the lowest Q-value of shallow gas model which has caused greater attenuation effect of seismic wave when passing through the shallow gas cloud area. Thus, detail seismic processing workflow including Q-compensation is necessary and is suggested for future works in order to compensate this effect.